The Selection of Optimal Gas Production Rate using Dynamic Reservoir Simulation in Field X - Rahmad Laksamana Pratama; Gerry Sasanti Nirmala; Edi Untoro; Jatmianto Jayeng Sugiantoro; Muhammad Ghazian R.A (Journal of Petroleum and Geothermal Technology, 2024)
Indonesian government has targeted a gas production rate of 12 BSCFD by 2030 to balance the energy demands and the carbon emission reduction. To achieve this goal, a comprehensive evaluation of a gas field will be carried out regarding Recovery Factor, Stable Production Period (Plateau Time), Total Production Period, and Profits using simulation programme. Dynamic Reservoir Simulation is an integrated field development simulation that combines physics, mathematics, reservoir engineering, and computer programming to analyze and predict the wells performance or how fluid flows through reservoir rocks to the surface over time under various operating conditions. There are stages in the simulation include Reservoir Model Creation, Initialization, History Matching, and Production Performance Forecasting. This research is a continuation of static reservoir modeling research done by LEMIGAS, which started by reinitializing the model and ended by forecasting the production performance of field X using several gas production flowrate scenarios to find out the optimal gas production flowrate for Field X in ten years period. The simulation result showed that the best gas production flowrate for a ten-year period is 3 mmscfd. It gives 78,505% recovery factors, with cumulative profit of $40,915,872 USD over a plateau period of 6.6 years.